Assessing the economic value of New Zealand design. (1st March 2020) - Brown, Anna; Mark, Simon; Petty, Margaret Maile
This article examines the challenges and complexities of assessing the value of design in contemporary economies, looking at New Zealand as a case study. Analysing the findings and recommendations of the first assessment of the economic value of design in New Zealand, published in 2017, this article seeks to bring greater clarity and understanding of the role of government and industry in a national design policy and ecosystem. Examining the performance and characteristics of New Zealand's design ecosystem and the unique characteristics of its design in the context of other countries with well-established design policies, this article argues that the adoption of a nationally coordinated approach to design education and innovation provides widespread benefits. Through the analysis of the 2017 assessment, this article offers insights into viable methodologies for the scholarly study of the value of design. The study concludes by critiquing government investment in design, emphasizing the importance of design to innovation and the performance of companies.